(untitled) (African Journal of Biomedical Research, 2019)
Myricetin belongs to the members of polyphenolic compounds that make up the flavonoid class, which possess antioxidant properties. Myricetin is mostly obtained from vegetables, fruits, nuts, berries, tea, and is also found in red wine. It is also similar structurally to quercetin, fisetin and luteolin and is known to possess similar functions as the other members in the flavonol class of flavonoids. The health benefits of myricetin cuts across being an anticarcinogen compound to its antiviral, antithrombotic, antidiabetic, antiatherosclerotic, neuroprotective and anti-inflammatory properties among others. It also plays a role as a cyclooxygenase 1 inhibitor, an antineoplastic agent, an antioxidant, a plant metabolite, a food component and a hypoglycemic agent. It is a hexahydroxyflavone and a 7-hydroxyflavonol. The 2D structure of myricetin was obtained from the PubChem database while the MarvinSketch software was used to effect the various structural modifications on the compound. The structural modifications entails the substitution of the OH group attached to the C1 of myricetin with different functional groups such as the C=O, C2H5, CH3, CHO, CONH2, H and OCH3 which were saved as mrv files. The saved mrv files for each 2D structures were converted into canonical SMILES with the aid of the Open Babel software while the pharmacokinetic parameters for each compound was predicted using the SwissADME server. Results from this study showed that the C2H5, CH3 and H analogues of myricetin showed a higher gastrointestinal absorption rate compared to their C=O, CHO, CONH2 and OCH3 counterparts. This result shows that the C2H5, CH3 and H analogues of myricetin might be more orally bioavailable compared to myricetin and the other modified analogues. Preclinical studies on these compounds are therefore recommended